Comparison of Methods in the Detection of ALK and ROS1 Rearrangements in Lung Cancer. Issue 4 (April 2015) - Rogers, Toni-Maree; Russell, Prudence A.; Wright, Gavin; Wainer, Zoe; Pang, Jia-Min; Henricksen, Leigh A.; Singh, Shalini; Stanislaw, Stacey; Grille, James; Roberts, Esteban; Solomon, Benjamin; Fox, Stephen B.
Abstract : Introduction: The use of targeted therapies toward specific oncogenic driver mutations has become a critical factor in the treatment of patients with lung cancer. It is therefore essential to utilize tests with high performance characteristics. Fluorescence in situ hybridization (FISH) is the standard method for detecting anaplastic lymphoma kinase (ALK ) and ROS1 rearrangements in non–small-cell lung cancer but the utility of other methods such as immunohistochemistry (IHC) and chromogenic in situ hybridization (CISH) is unclear. Methods: Three hundred and sixty-two lung cancer patients were tested with FISH, CISH, and IHC using three ALK antibodies (ALK1, 5A4, D5F3) and one ROS1 antibody in the detection of ALK and ROS1 rearrangements. Results: There was a 97.4% concordance (298 of 306) between FISH and CISH for detection of ALK rearrangements. The ROS1 rearrangement status had a 97% (291 of 300) concordance between CISH and FISH. ALK protein expression was observed in 6 of 341 samples with the ALK1 and 5A4 antibodies and 5 of 341 samples with D5F3. All three antibodies stained each of the ALK FISH-positive samples (100% sensitivity). ROS1 protein expression was observed in 2 of 322 samples. One of three samples with a ROS1 rearrangement by FISH showed ROS1 protein expression (33.3% sensitivity). Conclusion: Our findings show good correlation between FISH versus CISH in the detection of ALK and ROS1 rearrangements. FISH versus IHC showed good correlation in the detection of ALK rearrangements but showed weak correlation in the detection of ROS1 rearrangements. These results suggest CISH and IHC could be complimentary detection methods to FISH in the detection of ALK and ROS1 rearrangements.